Mutation identification and prediction for severe cardiomyopathy in Alström syndrome, and review of the literature for cardiomyopathy - Savas Dedeoglu; Elif Dede; Funda Oztunc; Asuman Gedikbasi; Gozde Yesil; Reyhan Dedeoglu (Orphanet Journal of Rare Diseases, 2022)
Abstract Objective Alström syndrome (ALMS) is a rare autosomal recessive genetic disorder that is caused by homozygous or compound heterozygous mutation in the ALMS1 gene. Dilated cardiomyopathy (DCM) is one of the well-recognized features of the syndrome ranging from sudden-onset infantile DCM to adult-onset cardiomyopathy, sometimes of the restrictive hypertrophic form with a poor prognosis. We aimed to evaluate severe cardiomyopathy in Alström syndrome in infancy and display susceptible specific mutations of the disease, which may be linked to severe DCM. Secondarily we reviewed published mutations in ALMS1 with cardiomyopathies in the literature. Method We represent new mutagenic alleles related to severe cardiomyopathy and cardiac outcome in this patient cohort. We evaluated echocardiographic studies of nine Turkish patients diagnosed with Alström syndrome (between 2014 and 2020, at age two weeks to twenty years). Thus, we examined the cardiac manifestations of a single-centre prospective series of nine children with specific ALMS mutations and multisystem involvement. All patients underwent genetic and biochemical testing, electrocardiograms, and echocardiographic imaging to evaluate systolic strain with speckle tracking. Results Four of the patients died from cardiomyopathy. Three patients (including three of the four fatalities) with the same mutation (c.7911dupC [p.Asn2638Glnfs*24]) had cardiomyopathy with intra-familial variability in the severity of cardiomyopathy. Global longitudinal strain, a measure of systolic contractile function, was abnormal in all patients that can be measured. Conclusion Cardiac function in ALMS patients with infantile cardiomyopathy appears to have different clinical spectrums depending on the mutagenic allele. The c.7911dupC (p. Asn2638Glnfs*24) mutation can be related to severe cardiomyopathy. Parents can be informed and consulted about the progression of severe cardiomyopathy in a child carrying this mutagenic allele.